2023
DOI: 10.4049/jimmunol.2200465
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Negative Regulation of Inflammasome Activation by TRAF1 Can Limit Gout

Abstract: Secretion of IL-1β, a potent cytokine that plays a key role in gout pathogenesis, is regulated by inflammasomes. TRAF1 has been linked to heightened risk to inflammatory arthritis. In this article, we show that TRAF1 negatively regulates inflammasome activation to limit caspase-1 and IL-1β secretion in human and mouse macrophages. TRAF1 reduces linear ubiquitination and subsequent oligomerization of the adapter protein, ASC. i.p. injection of monosodium urate crystals resulted in increased inflammatory cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Mice with macrophages deficient in caspase-1, ASC or NLRP3 were defective in MSU crystal-induced IL-1β secretion [ 25 ]. Intriguingly, a new study revealed that Tumor necrosis factor receptor (TNFR)-associated factor 1 (TRAF1), an immune signaling adapter involved in regulation of NF-κB activation, negatively regulates inflammasome activation and limits joint swelling and inflammation in a model of MSU-crystal induced gout [ 26 ]. Moreover, several studies have found that certain NLRP3 polymorphisms, most notably rs3806268 and rs10754558, were associated with an increased susceptibility to gout [ 27 , 28 ].…”
Section: Nod-like Receptors In Goutmentioning
confidence: 99%
“…Mice with macrophages deficient in caspase-1, ASC or NLRP3 were defective in MSU crystal-induced IL-1β secretion [ 25 ]. Intriguingly, a new study revealed that Tumor necrosis factor receptor (TNFR)-associated factor 1 (TRAF1), an immune signaling adapter involved in regulation of NF-κB activation, negatively regulates inflammasome activation and limits joint swelling and inflammation in a model of MSU-crystal induced gout [ 26 ]. Moreover, several studies have found that certain NLRP3 polymorphisms, most notably rs3806268 and rs10754558, were associated with an increased susceptibility to gout [ 27 , 28 ].…”
Section: Nod-like Receptors In Goutmentioning
confidence: 99%
“…Primary bone marrow derived macrophages (BMDMs) were prepared from C57/Bl6 wildtype (WT) and TRAF1-/-mice and cultured, as described previously [10,11]. Briefly, femur and tibia of mice were flushed and cultured in RPMI 1640 (Sigma) supplemented with 10% fetal bovine serum (Wisent), 2-Mercapthoethanol (Gibco), L-Glutamine (Sigma), Pyruvate (Sigma), penicillin (Sigma), streptomycin (Sigma), non-essential amino acids (Gibco) and 25% L929-conditioned media.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…In a more recent study, we employed a monosodium urate (MSU) crystal-induced model of gout in mice and reported that TRAF1 deficient mice exhibited a significant increase in joint swelling and inflammatory cell infiltration into the synovium compared to wildtype littermates [10]. Mechanistically, TRAF1 lowered IL-1β secretion and inhibited NLRP3 inflammasome assembly in macrophages by limiting the linear ubiquitination of the adapter protein, ASC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, corticosteroids are only considered when NSAIDs and/or colchicine are not applicable. IL‐1 is a potent multifunctional cytokine that plays a key role in gout pathogenesis 25 . Drugs targeting IL‐1 mainly include recombinant IL‐1 receptor antagonist (anakinra), neutralizing anti‐IL‐1β antibodies (canakinumab), and IL‐1β traps (rilonacept) 26 .…”
Section: Figurementioning
confidence: 99%
“…IL-1 is a potent multifunctional cytokine that plays a key role in gout pathogenesis. 25 Drugs targeting IL-1 mainly include recombinant IL-1 receptor antagonist (anakinra), neutralizing anti-IL-1β antibodies (canakinumab), and IL-1β traps (rilonacept). 26 If colchicine, NSAIDs, and corticosteroids are not applicable or have poor efficacy for gout flare patients, IL-1 targeting drugs can be considered for treatment.…”
mentioning
confidence: 99%